Analisis Perilaku Kerja Yang Aman dalam Penyemprotan Pestisida Berdasarkan Health Belief Model pada Petani Penyemprot Pestisida (Studi Kasus di Kelurahan Tuatuka, Kecamatan Kupang Timur, Kabupaten Kupang) - Eva Magdalena Elisabeth Taklal; Luh Putu Ruliati; Noorce Ch. Berek; Jacob M. Ratu (KOLONI, 2026)
Pesticide spraying is an agricultural activity that poses potential health risks due to exposure to hazardous chemical substances. The adoption of safe work practices is essential to minimize the risk of pesticide poisoning; however, such practices may be influenced by individual perceptions as described in the Health Belief Model. This study aimed to examine the association between perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action and safe work behavior among pesticide applicators in Tuatuka Village, East Kupang District, Kupang Regency. An analytical quantitative study with a cross-sectional design was conducted among 92 pesticide-spraying farmers selected through total sampling. Data were analyzed using univariate and bivariate analyses with the Chi-square test at a 95% confidence level (α = 0.05). The findings revealed that 63.0% of respondents demonstrated safe work behavior. Bivariate analysis showed a significant association between perceived benefits and safe work behavior (p = 0.000). In contrast, perceived susceptibility (p = 0.424), perceived severity (p = 0.068), perceived barriers (p = 0.058), and cues to action (p = 0.185) were not significantly associated with safe work behavior. These findings suggest that perceived benefits play a pivotal role in encouraging the adoption of safe work practices during pesticide application. Strengthening health promotion and educational interventions that emphasize the benefits of safe work practices may contribute to improving occupational safety and health among pesticide applicators.